What's love got to do with it [videorecording (DVD)] - Gibson, Brian, 1944-2004; Bassett, Angela; Fishburne, Laurence, III, 1961-; Turner, Tina (Touchstone Home Video ; Distributed by Buena Vista Home Entertainment, 1999)
The turbulent relationship of Ike and Tina Turner eventually forces Tina to leave and find the courage to believe in herself.